Evaluation of Chemical Characteristics of Swimming Pool Water and Poly(dimethyldiallylammonium chloride) Coagulation with Inactive Cryptosporidium parvum Oocysts in Pool Water - Yuan, Tao; Lu*, Ping; Feng, Qiyan; Li, Ting; Sun, Yue (Asian Journal of Chemistry, 2013)
Cryptosporidiosis has threatened public health significantly in swimming pool. Swimming pool water samples were collected and analyzed for chemical constituents from 40 swimming pools geographically distributed in one city in China, during one swimming season. Results showed investigated swimming pool water pH and free chlorine was in the recommended range, while hardness and alkalinity was higher. Three representative pool water was generated based on statistical analysis. Oxidation reduction potential (ORP) in the range of 800 to 880 for pools implied the investigated swimming pool water quality was acceptable. Zeta potential titration results show an upward trend of zeta potential with increased poly(dimethyldiallylammonium chloride) (pDADMAC) concentration, which indicated poly(dimethyldiallylammonium chloride) was a promising pool water treatment coagulant to help control cryptosporidiosis in pools. Additionally, poly(dimethyldiallylammonium chloride) could perform well in the three representative types of pool water with different chemical characteristics.